Promising effects of 33 to 36 Fr. bougie calibration for laparoscopic sleeve gastrectomy: a systematic review and network meta-analysis - Po-Chih Chang (Nature Portfolio, 2021)
Abstract The standard size of bougie for laparoscopic sleeve gastrectomy (LSG) is not yet established. Therefore, a systematic review and network meta-analysis were conducted to assess the weight loss effects and associated complications of LSG for patients with morbid obesity, based on different bougie sizes. A total of 15 studies were reviewed in this systemic review and network meta-analysis (2,848 participants), including RCTs and retrospective studies in PubMed, and Embase until September 1, 2020. The effectiveness of different bougie calibration sizes was assessed based on excess weight loss (EWL), total complications, and staple line leak. Within this network meta-analysis, S-sized (≤ 32 Fr.) and M-sized (33–36 Fr.) bougies had similar effects and were associated with the highest EWL improvement among all different bougie sizes (S-sized: standardized mean difference [SMD], 10.52; 95% confidence interval [CI] − 5.59 to  − 26.63, surface under the cumulative ranking curve [SUCRA], 0.78; and M-sized: SMD, 10.16; 95% CI − 3.04–23.37; SUCRA, 0.75). M-sized bougie was associated with the lowest incidence of total complications (M-sized: odds ratio, 0.43; 95% CI, 0.16–1.11; SUCRA, 0.92). Based on our network meta-analysis, using M-sized bougie (33–36 Fr.) is an optimal choice to balance the effectiveness and perioperative safety of LSG in the clinical practice.